Macrocyclic peptide inhibitors for the protein–protein interaction of Zaire Ebola virus protein 24 and karyopherin alpha 5. Issue 24 (2nd June 2017) - Song, Xiao; Lu, Lu-yi; Passioura, Toby; Suga, Hiroaki
Abstract : Describes the identification of macrocyclic peptide inhibitors of the ebola VP24 protein–karyopherin alpha 5 protein–protein interaction with nanomolar affinity for VP24. Abstract : Ebola virus infection leads to severe hemorrhagic fever in human and non-human primates with an average case fatality rate of 50%. To date, numerous potential therapies are in development, but FDA-approved drugs or vaccines are yet unavailable. Ebola viral protein 24 (VP24) is a multifunctional protein that plays critical roles in the pathogenesis of Ebola virus infection, e.g. innate immune suppression by blocking the interaction between KPNA and PY-STAT1. Here we report macrocyclic peptide inhibitors of the VP24–KPNA5 protein–protein interaction (PPI) by means of the RaPID (Random non-standard Peptides Integrated Discovery) system. These macrocyclic peptides showed remarkably high affinity to recombinant Zaire Ebola virus VP24 (eVP24), with a dissociation constant in the single digit nanomolar range, and could also successfully disrupt the eVP24–KPNA interaction. This work provides for the first time a chemical probe capable of modulating this PPI interaction and is the starting point for the development of unique anti-viral drugs against the Ebola virus.